49.6k views
4 votes
I need someone to explain how I got this answer please

I need someone to explain how I got this answer please-example-1
User SudarakaR
by
4.6k points

1 Answer

3 votes

Using Pythagoras' theorem;


\begin{gathered} 8^2=x^2+y^2----(1) \\ y^2=z^2+6^2----(2) \\ x^2=z^2+2^2-----(3) \end{gathered}
\begin{gathered} From\text{ \lparen1\rparen;} \\ y^2=8^2-x^2----(a) \\ Sunstituting\text{ \lparen a\rparen into \lparen2\rparen} \\ 8^2-x^2=z^2+6^2 \\ x^2=-z^2+28----(4) \end{gathered}
undefined

User BraveNewMath
by
5.2k points